Hazard analysis critical control point (HACCP) implementation in the small and medium-sized food manufacturing enterprises: a case study of ten companies / Muhammad Izzat Zulkifly - Zulkifly, Muhammad Izzat (2009)
Today's food supply has become more global and more food products have emerged on to the market. Thus consumer awareness of the quality and safety of the foods has increased tremendously. Realizing the current trends, many food manufacturers, including food SMEs, have acknowledged that a combination of food quality and safety approaches and processing methods are crucial in ensuring the best quality and safety of foods produced before they reach the end users. They have therefore turned their attention to a system that has been widely accepted locally and internationally called HACCP. This study investigates the Malaysian food SMEs' main motive in implementing the system. It also assesses the effectiveness of the system's implementation by the SMEs through the managements' and employees' commitment and the benefits of the system on the companies' productivity. Sample populations for this study were among the food SMEs that had implemented HACCP in the Klang Valley area. The list of companies which participated was obtained after final confirmation had been made. The face-to-face interview approach used among the representative managers provided truly significant and in-depth information for this study. The interview transcription and analysis signified that the 'customer requirement' was the major motive of food SMEs.in implementing HACCP and outnumbered the other motives, namely perception of good practice, internal efficiency and regulatory requirements. In addition, it was found that the managements' and employees' commitment after HACCP implementation was fairly satisfactory and HACCP offered numerous benefits for the companies' productivity. The managers confessed that a few obstacles were encountered during the implementation, but viewed them as a common situation in any business operation. Managers' perceptions from the interviews were validated through quantitative information obtained from production line employees in each participating company. Employees' claimed that they were satisfied with the managements' commitment and reported that they were pleased with and committed to their job even after HACCP took place in their organization. They also admitted that productivity experienced much improvement from HACCP implementation.